Cyclic Technology for Obtaining Double, Triple Superphosphate and Concentrated Nitrogen-Phosphorus Fertilizer from Low-Grade Phosphorites of Central Kyzylkum - Abdullayev S.S; Mamajonov O.A; Alimov U.K; Ortiqova S.S (Genius Journals, 2022)
This article presents data from studies on the processing of low-grade phosphorites into unilateral and complex phosphorus fertilizers in a cyclic way. Based on the neutralization of acidic products of monocalcium phosphate isolated from the crystallization process, off-balance ore and limestone, double and triple superphosphates were obtained with a content of: Р2О5tot. from 44.43 to 47.09%; Р2О5usv. : Р2О5tot. = 94.24-97.86% and Р2О5tot. from 50.05 to 53.38%; Р2О5usv. : Р2О5tot. = 97.08-99.59%, respectively. And by neutralizing acid monocalcium phosphate with ammonia to pH = 4.5-4.8, NP-fertilizers were obtained with the content (wt.%): N from 8.97 to 10.12; Р2О5 tot. from 55.18 to 56.64 with relative water form Р2О5 aq. from 79.85 to 85.91%.
Keywords: phosphorites of the Central Kyzylkum; phosphoric acid; kinetics; NP fertilizer